Aerodynamic stability of road vehicles in dynamic pitching motion - Tsubokura, Makoto; Cheng, See Yuan; Nakashima, Takuji; Okada, Yoshihiro; Nouzawa, Takahide; Doh, Deog-Hee (Elsevier B.V., 2013)
The main object of the present study is to investigate numerically the mechanism of aerodynamic damping of pitching oscillation in sedan-type vehicles. The transient numerical solver employed is based on the Large Eddy Simulation (LES) method. Whilst, the Arbitrary Lagrangian-Eulerian (ALE) method was used to realize the vehicle motion during dynamic pitching and fluid flow coupled simulations. Validation of the numerical method was done by comparing the flow structures obtained from the LES to the corresponding flow structures observed in the wind tunnel measurements. Two vehicle models with basic sedan-type automobile shape were created to study the influences of upper body geometry on the aerodynamic pitching stability of sedan-type vehicle. In addition, the credibility of modeling of automotive aerodynamics by simple bluff body models was verified. For the sedan-type models investigated, the trailing vortices that shed from the A-pillar and C-pillar edges were found to produce the opposite tendencies on how they affect the aerodynamic pitching stability of the models. In particular, the vortex shed from the A-pillar edge tended to enhance the pitching oscillation, while the vortex shed from the C-pillar edge tended to suppress it. Hence, the vehicle with rounded A-pillar and angular C-pillar exhibited a higher aerodynamic damping than the vehicle with the opposite A- and C-pillars configurations. The aerodynamic damping mechanism has been proposed based on the results of flow visualization on the phase-averaged flow properties.